Using SenseCam, A Wearable Camera, to Alleviate Autobiographical Memory Loss - Emma Berry (Microsoft Research, 2007)
SenseCam may help people with memory impairment retrieve and consolidate past events, and this may improve confidence & reduce anxiety Undertaking functional imaging studies to explore the activation associated with viewing SenseCam images Collaborations planned with a number of academic partners Now is a good time for psychologists to collaborate with technologists to develop and explore the use of technology in cognitive and emotional rehabilitation
Presentation at the British Psychological Society Annual Conference 2007, York